Synthesis, and Molecular Structure Investigations of a New s-Triazine Derivatives Incorporating Pyrazole/Piperidine/Aniline Moieties - Ihab Shawish; Saied M. Soliman; Matti Haukka; Ali Aldalbahi; Assem Barakat; Ayman El-Faham (Crystals, 2021)
In this work, we synthesized two new s-triazine incorporates pyrazole/piperidine/aniline moieties. Molecular structure investigations in the light of X-ray crystallography combined with Hirshfeld and DFT calculations were presented. Intermolecular interactions controlling the molecular packing of 4-(3,5-dimethyl-1H-pyrazol-1-yl)-N-phenyl-6-(piperidin-1-yl)-1,3,5-triazin-2-amine; 5a and N-(4-bromophenyl)-4-(3,5-dimethyl-1H-pyrazol-1-yl)-6-(piperidin-1-yl)-1,3,5-triazin-2-amine; 5b were analyzed using Hirshfeld calculations. The most dominant interactions are the H...H, N...H and H...C contacts in both compounds. The N...H and H...C interactions in 5a and the N...H, Br...H and H...H interactions in 5b are the most important. In addition, DFT calculations were used to compute the molecular structures of 5a and 5b; then, their electronic properties, as well as the 1H- and 13C-NMR spectra, were predicted. Both compounds are polar where 5a (1.018 Debye) has lower dipole moment than 5b (4.249 Debye). The NMR chemical shifts were calculated and very good correlations between the calculated and experimental data were obtained (R2 = 0.938–0.997).